2008
DOI: 10.1111/j.1467-629x.2007.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a virtual learning environment into a second‐year accounting course: determinants of overall student perception

Abstract: Rapid acceptance of, and changes in, information technology are revolutionizing the way educators teach and students learn. This study reports on the use of Blackboard as a tool for creating a virtual learning environment (VLE). Responses from undergraduate accounting students in New Zealand provide data on the use of the VLE as a learning aid. Findings suggest that the students have openly embraced the VLE and support its adoption by faculty members in other courses. However, students appear unwilling to acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 16 publications
4
53
0
5
Order By: Relevance
“…Synchronous forums allow for a much higher level of interactivity than time-delayed or asynchronous forums. Wells et al (2008) find, however, that students are reluctant to engage in synchronous communication even though they embrace online course materials. Love and Fry (2006) suggest that this is because students consider online materials as a safety net rather than a supplementary learning tool.…”
Section: Online Learning Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchronous forums allow for a much higher level of interactivity than time-delayed or asynchronous forums. Wells et al (2008) find, however, that students are reluctant to engage in synchronous communication even though they embrace online course materials. Love and Fry (2006) suggest that this is because students consider online materials as a safety net rather than a supplementary learning tool.…”
Section: Online Learning Literature Reviewmentioning
confidence: 99%
“…In contrast, Perera and Richardson (2010) find the quantity of material accessed via asynchronous forums and the quantity of asynchronous discussion interaction, rather than time spent online per se, positively impacts final exam performance. Others find students perceive synchronous forums as either providing them with core material to fall back on or as a tutor communication (Love and Fry 2006), and as a result students are unwilling to participate in synchronous online activities (Wells et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ginns and Ellis (2007) acknowledged the increasing pressure for greater integration of new technology into the student learning experience. Wells, de Lange and Fieger (2008) found that the use of technology in educational settings assists in the achievement of learning outcomes. Buzzetto-More (2008) and Sanders & Morrison-Shetlar (2002) report that student attitudes toward technology are influential in determining the educational benefits of online learning resources and experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…El uso de entornos virtuales de aprendizaje facilita un enfoque de aprendizaje más centrado en el estudiantado y permite a éste asumir un papel más activo al no ser mero receptor de información. Todos estos aspectos pueden culminar en un aprendizaje de mejor calidad (Potter y Johnston, 2006;Wells et al, 2008), especialmente cuando se combinan con la enseñanza tradicional en el aula (McVay et al, 2008).…”
Section: Campus Virtualunclassified